ANALISIS HUBUNGAN MANAJEMEN USAHATANI PADI SAWAH DENGAN TINGKAT KEBERHASILAN GAPOKTAN SERUMPUN (Studi Kasus Gapoktan Serumpun Kota Gorontalo) - Ratnasari, Dian; Rauf, Asda; Boekoesoe, Yuriko (Agrinesia: Jurnal Ilmiah Agribisnis, 2017)
This research aims to analyze the implementation of management of rice field paddy farming business at Gapoktan Serumpun, City of Gorontalo and the relation between management of rice field paddy farming business with level of successfulness of Gapoktan Serumpun, Village of Dembe Jaya, Sub-district of Kota Utara, City of Gorontalo, Province of Gorontalo. This research is conducted at Gapoktan Serumpun, Village of Dembe Jaya, Sub-district of Kota Utara, City of Gorontalo from April to June 2017 with 48 farmers as research samples. This research applies survey method. Research data are analyzed by descriptive analysis with percentage formula and Pearson Correlation analysis. Research finding reveals that based on assessment of farmer group and farmer as individual, management of rice field paddy farming business Gapoktan Serumpun, Village of Dembe Jaya, Sub-district of Kota Utara, City of Gorontalo remains in Very Good category with percentage value of 87% and 85%. Meanwhile, success of Gapoktan Serumpun, Village of Debe Jaya, Sub-district of Kota Utara, City of Gorontalo as learning unit, cooperation unit and production unit as well as enterprise unit shows good category with value of percentage of 81%. Then, finding of research about relation between management of farming business with level of successfulness of Gapoktan Serumpun shows there is relation of 0.70 at level of failure for 0.01 and it is included in category of strong relation.